Cardiometabolic risk factors in the Swedish Werlabs cohort based on self-initiated health screening: cohort profile - Peter Ueda; Kerstin Brismar; Anna Norhammar; Daniel Peter Andersson; Hannah Coudé Adam; Omid Hajimirsadeghi; Lovisa Krantz; Nadia Bandstein Forsberg (BMJ Open)
Purpose There is limited research on individuals undergoing self-initiated health examinations, and the Werlabs cohort will be a base for such research.Participants All individuals aged 18 or older who had undertaken a self-initiated health examination at Werlabs AB with at least one recorded value of creatinine or cholesterol in Sweden (from 1 January 2015 through 31 December 2023) was included. Medical history and anthropometric measurements were self-reported through an online questionnaire. We describe cohort baseline characteristics, demographic variables and cardiometabolic risk factors.Findings to date The study population includes 149 556 individuals who provided at least one health screening. The median (IQR) age was 43 (33–54) years and 54% were women. The most common self-reported chronic disease was hypertension (4.5%), followed by cardiovascular disease (0.9%) and 12.6% reported values of obesity. The prevalence was 2.1% for diabetes, 1.2% for kidney disease (including an estimated glomerular filtration rate of <60 mL/min/1.73 m2), 57.8% for a low-density lipoprotein cholesterol level of >3.0 mmol/L and 4.1% for anaemia (haemoglobin <120 g/L and <130 g/L for women and men, respectively). Interestingly, 1.5% of the individuals had a glucose measurement of >7.0 mmol/L, without reporting a previous diagnosis of diabetes. In an analysis restricted to 621 individuals with recorded blood pressure data between the age of 40 and 70 years and without existing cardiovascular disease, diabetes or kidney disease, 35,4% were classified as high or very high cardiovascular risk according to the 2021 ESC guidelines on cardiovascular disease prevention and with lipid levels that made them eligible for lipid-lowering therapy.Future plans The Werlabs cohort comprises a rather healthy and young population that can provide opportunities for future studies on individuals undergoing self-initiated health examinations and has the potential to impact treatment of cardiometabolic risk factors.